Does the recent increase in HIV diagnoses among men who have sex with men in the UK reflect a rise in HIV incidence or increased uptake of HIV testing?. Issue 2 (7th November 2006) - Dougan, Sarah; Elford, Jonathan; Chadborn, Timothy R; Brown, Alison E; Roy, Kirsty; Murphy, Gary; Gill, O Noel
Abstract : Objectives: To determine whether the increase in HIV diagnoses since 1997 among men who have sex with men (MSM) in the UK reflects a rise in HIV incidence or an increase in HIV testing. Methods: Estimates of HIV incidence were derived using data from UK HIV surveillance systems (HIV diagnoses; CD4 surveillance; unlinked anonymous surveys) for 1997–2004. Data on HIV testing were provided by KC60 statutory returns, voluntary testing and unlinked anonymous surveys in sentinel genitourinary medicine (GUM) clinics. Results: HIV diagnoses among MSM in the UK rose by 54% between 1997 and 2004 (from 1382 to 2124), with variation by age and geographical location. The number of HIV diagnoses among MSM <35 years of age in London showed no increase, but in all other groups it increased. Throughout the UK, uptake of HIV testing increased significantly among MSM attending GUM clinics between 1997 and 2004, including "at-risk" MSM (p<0.001). Direct incidence estimates (serological testing algorithm for recent HIV seroconversion assay) provided no evidence of a statistically significant increase or decrease in HIV incidence. Indirect estimates suggested that there may have been a rise in HIV incidence, but these estimates were influenced by the increased uptake of HIV testing. Conclusions: The number of HIV diagnoses increased among MSM in the UK between 1997 and 2004, except among younger MSM in London, in whom there was no change. The increase in HIV diagnoses among MSM in the UK since 1997 seems to reflect an increase in HIV testing rather than a rise in HIV incidence.